Catalase impairs Leishmania mexicana development and virulence. Issue 1 (1st January 2021) - Sádlová, Jovana; Podešvová, Lucie; Bečvář, Tomáš; Bianchi, Claretta; Gerasimov, Evgeny S.; Saura, Andreu; Glanzová, Kristýna; Leštinová, Tereza; Matveeva, Nadezhda S.; Chmelová, Ľubomíra; Mlacovská, Denisa; Spitzová, Tatiana; et al.
ABSTRACT: Catalase is one of the most abundant enzymes on Earth. It decomposes hydrogen peroxide, thus protecting cells from dangerous reactive oxygen species. The catalase-encoding gene is conspicuously absent from the genome of most representatives of the family Trypanosomatidae. Here, we expressed this protein from the Leishmania mexicana Β-TUBULIN locus using a novel bicistronic expression system, which relies on the 2A peptide of Teschovirus A . We demonstrated that catalase-expressing parasites are severely compromised in their ability to develop in insects, to be transmitted and to infect mice, and to cause clinical manifestation in their mammalian host. Taken together, our data support the hypothesis that the presence of catalase is not compatible with the dixenous life cycle of Leishmania, resulting in loss of this gene from the genome during the evolution of these parasites.